Biosynthesis of Menaquinone in E. coli: Identification of an Elusive Isomer of SEPHCHC. (28th July 2022) - Fries, Alexander; Mazzaferro, Laura S.; Bisel, Philippe; Hubrich, Florian; Andexer, Jennifer N.; Müller, Michael
Abstract: In the biosynthesis of menaquinone in bacteria, the thiamine diphosphate‐dependent enzyme MenD catalyzes the decarboxylative carboligation of α‐ketoglutarate and isochorismate to (1 R, 2 S, 5 S, 6 S )‐2‐succinyl‐5‐enolpyruvyl‐6‐hydroxycyclohex‐3‐ene‐1‐carboxylate (SEPHCHC). The regioisomer of SEPHCHC, namely (1 R, 5 S, 6 S )‐2‐succinyl‐5‐enolpyruvyl‐6‐hydroxycyclohex‐2‐ene‐1‐carboxylate (iso‐SEPHCHC), has been considered as a possible product, however, its existence has been doubtful due to a spontaneous elimination of pyruvate from SEPHCHC to 2‐succinyl‐6‐hydroxy‐2, 4‐cyclohexadiene‐1‐carboxylate (SHCHC). In this work, the regioisomer iso‐SEPHCHC was distinguished from SEPHCHC by liquid chromatography‐tandem mass spectrometry. Iso‐SEPHCHC was purified and identified by NMR spectroscopy. Just as SEPHCHC remained hidden as a MenD product for more than two decades, its regioisomer iso‐SEPHCHC has remained until now. Abstract : Elusive isomer : The shikimate pathway has been studied over decades, but the metabolite iso‐SEPHCHC remained hidden until now.